2020
DOI: 10.1016/j.foodres.2020.109567
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese cacholeira blood sausage: A first taste of its microbiota and volatile organic compounds

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
(76 reference statements)
4
18
0
Order By: Relevance
“…Variations from batch to batch in yeast species abundances were observed, in particular for D. hansenii which was less abundant in the March batch for example, while Y. divulgata was only identified in the latter batch, and C. zeylanoides was more prevalent in the February batch. Such variations have been previously reported in other traditional fermented foods of animal origin (Viljoen et al 2003;Belleggia et al 2020a) and are not surprising given the fact that the yeast mycobiota originates from the raw materials and the factory environment. It is worth mentioning that several species found in the present study have been rarely reported in fermented meats, such as Y. divulgata, Trametes versicolor and C. sake.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Variations from batch to batch in yeast species abundances were observed, in particular for D. hansenii which was less abundant in the March batch for example, while Y. divulgata was only identified in the latter batch, and C. zeylanoides was more prevalent in the February batch. Such variations have been previously reported in other traditional fermented foods of animal origin (Viljoen et al 2003;Belleggia et al 2020a) and are not surprising given the fact that the yeast mycobiota originates from the raw materials and the factory environment. It is worth mentioning that several species found in the present study have been rarely reported in fermented meats, such as Y. divulgata, Trametes versicolor and C. sake.…”
Section: Discussionsupporting
confidence: 66%
“…While certain mold species may contribute to the organoleptic properties of Salame Piemonte, as reported for C. cladosporioides that was considered as a beneficial fungal species in Portuguese and South American sausages (Parussolo et al 2019a;Belleggia et al 2020a), other species are known mycotoxin producers and should be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes some of these products and their origins. Many countries where sausages and dry-meat foods have been studied belong to the Mediterranean area [ 8 , 36 , 37 , 38 , 39 , 40 , 41 ], but dry-cured meat or sausages are prepared and consumed by millions of people worldwide and also in other European countries such as Denmark [ 42 ], Norway [ 43 ], Austria [ 7 ], the United Kingdom [ 6 ], and Portugal [ 44 ]. Even in places such as Argentina [ 45 ] or China [ 46 , 47 ], among many others, meat products are manufactured in which it is possible to find D. hansenii yeasts, supposedly contributing to the final organoleptic characteristics of the food.…”
Section: Debaryomyces Hansenii Is One Of the Most Abundant Yeasts In Sausages And Dry-meat Productsmentioning
confidence: 99%
“…However, the content of benzaldehyde (almond, burnt sugar) and benzeneacetaldehyde (honey-like) from the phenylalanine amino acid degradation improves the flavor of dry sausages [22]. In addition, 3-methylbutanal (roasted notes) is considered one of the strongest odorants in dry-fermented sausages [23]. The addition of 2% chia seeds could also promote the degradation of lipids because there was an increase in the total number of compounds compared with the rest of the batches.…”
Section: Volatile Compoundsmentioning
confidence: 99%